(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Article explores the theoretical foundations, methodological principles, and pedagogical advantages of the Integrated Course in Foreign Language Teaching (ICFLT). The integrated approach combines linguistic, communicative, intercultural, and digital competences into a unified instructional system, promoting holistic language development rather than fragmented skill acquisition. The study analyzes modern integration models, including CLIL, task-based integration, multimodal integration, and digital-mobile integration. Psychological mechanisms supporting integrative learning are explained, and the effectiveness of ICFLT in enhancing communicative competence, learner autonomy, and intercultural awareness is demonstrated. Practical recommendations for implementing integrated courses in schools and universities are offered.